2013
DOI: 10.1088/0004-637x/768/2/116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Members in the Central and Outer Regions of Galaxy Clusters

Abstract: The caustic technique measures the mass of galaxy clusters in both their virial and infall regions and, as a byproduct, yields the list of cluster galaxy members. Here we use 100 galaxy clusters with mass M 200 ≥ 10 14 h −1 M ⊙ extracted from a cosmological N -body simulation of a ΛCDM universe to test the ability of the caustic technique to identify the cluster galaxy members. We identify the true threedimensional members as the gravitationally bound galaxies. The caustic technique uses the caustic location i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 67 publications
(92 reference statements)
2
69
0
1
Order By: Relevance
“…Deviations from spherical symmetry result in a 50% uncertainty in individual cluster profiles. Serra & Diaferio (2013), also using cosmological simulations, showed that this technique can identify cluster galaxies with a completeness fraction of 95%. Observationally, galaxies outside these caustics are identified as not being bound to the cluster.…”
Section: Phase-space Detectionmentioning
confidence: 96%
“…Deviations from spherical symmetry result in a 50% uncertainty in individual cluster profiles. Serra & Diaferio (2013), also using cosmological simulations, showed that this technique can identify cluster galaxies with a completeness fraction of 95%. Observationally, galaxies outside these caustics are identified as not being bound to the cluster.…”
Section: Phase-space Detectionmentioning
confidence: 96%
“…As a byproducts, tho technique identifies the cluster members, namely those galaxies whose radial velocity is smaller than the escape velocity at a given clustercentric radius. Numerical simulations show that the cluster membership obtained using this technique has an interloper contamination of only 2% within R200 (Serra & Diaferio 2013).…”
Section: Cluster Membershipmentioning
confidence: 99%
“…Contamination by foreground and background objects is significantly reduced relative to samples based on photometric redshifts (e.g., Geller et al 2014;Hwang et al 2014). Applying the caustic technique (Diaferio & Geller 1997;Diaferio 1999;Serra & Diaferio 2013) to the spectroscopic sample (see Section 3) identifies cluster members; the completeness of membership determination from the caustic technique is 95% within 3R 200 based on numerical simulations (Serra & Diaferio 2013). For bright A2029 galaxies we compiled redshifts from the SDSS spectroscopic survey.…”
Section: Spectroscopymentioning
confidence: 99%
“…We use the caustic technique (Diaferio & Geller 1997;Diaferio 1999;Serra & Diaferio 2013) to analyze the data. Simulations by Serra & Diaferio (2013) show that the caustic technique recovers 95% of the clusters members within 3R 200 for mock catalogs with ∼1000 galaxies in the field of view and ∼180 members per cluster; these objects all appear within the caustics. The interloper contamination from non-member galaxies that appear within the caustics is~2% at R 200 and~8% at 3R 200 .…”
Section: Cluster Membershipmentioning
confidence: 99%